Administração do 8-OH-DPAT no septo dorso lateral de camundongos submetidos ao labirinto em cruz elevado promove efeito ansiolítico que é revertido pelo pré-tratamento local com WAY100635 - Silva, Helvia Arandas Monteiro e (Universidade Federal de São Carlos, 2010)
Research on anxiety often involves the use of animal models for investigation of therapeutic compounds. Thus, the elevated plus maze (EPM) is one of the most commonly model used in research involving anxiety and it has been validated for rats and mice. Serotonin (5-HT) is a neurotransmitter involved not only in anxiety but also in other disorders. Some reports show that increasing the potency and selectivity of agonists demonstrates that the 5-HT1A receptors are involved in mechanisms of behavioral changes, for example, anxiety. Therefore, the aim of the present study was to evaluate the effects of agonist and antagonist of 5-HT1A receptors, administered intradorsolateral septum in mice exposed by LCE. The behavioral effects were examined by conventional and ethological analysis of the sessions (tripped) test. In experiment 1, the highest dose of the agonist 8-OH-DPAT (10nmol) induced anxiolytic effect, whereas the lowest dose tested (5.6 nmol) did not provide effect. In experiment 2, injection of the antagonist WAY-100 635 (5.6 nmol) did not alter any of the conventional indices of anxiety. In experiment 3, pretreatment with WAY-100 635 (5.6 nmol) reversed the anxiolytic effect of the two doses of 8-OH-DPAT (5.6 and 10nmol). The results showed that the anxiolytic effect promoted by the agonist of 5-HT1A receptors was blocked by local administration of WAY-100 635, the same receptor antagonist.
Keywords: Neuropsicofarmacologia; Ansiedade; Sistema nervoso - cirurgia; Serotonina; Comportamento animal; CIENCIAS BIOLOGICAS::FISIOLOGIA